Museologies at the Service of Difference and the Specialty Language: An Integrative Review on the Resonances of the Term "Difference" in Sociomuseology (Cadernos de Sociomuseologia, 2025)
This paper carries out a literature review on the resonances of the term difference within the scope of sociomuseology, aiming to understand some configurations of the specialized language in this School of Thought. The aim is to understand how difference, as a term and concept, has been mobilized, problematizing the specificities and terminological challenges. Using a qualitative and quantitative methodology based on an integrative literature review, the universe of analysis is the texts (editorials, articles, and documents) published in the magazine Cadernos de Sociomuseologia (Sociomuseology Notebooks)(1993-2023) and the theses defended in the PhD in Museology at Universidade Lusófona (2008-2023). This paper highlights an increase in the incidence of the term difference in the texts analyzed and a polysemic approach, with an increasingly explicit dialogue with decolonial epistemologies and interculturality. Finally, it identifies the three authors and concepts most cited in the review: Mário Moutinho with the concept of “right to difference”; Maria Célia Teixeira Moura Santos and “respect for difference”; and Paulo Freire, based on the concepts “difference from the other” and “respect for difference”.Keywords: Sociomuseology. Terminology. Difference.